2003
DOI: 10.1182/blood-2002-07-2315
|View full text |Cite
|
Sign up to set email alerts
|

The tetrapeptide AcSDKP, an inhibitor of primitive hematopoietic cell proliferation, induces angiogenesis in vitro and in vivo

Abstract: The tetrapeptide acetyl-Ser-Asp-Lys-Pro (AcSDKP), purified from bone marrow and constitutively synthesized in vivo, belongs to the family of negative regulators of hematopoiesis. It protects the stem cell compartment from the toxicity of anticancer drugs and irradiation and consequently contributes to a reduction in marrow failure. This current work provides experimental evidence for another novel biologic function of AcSDKP. We report that AcSDKP is a mediator of angiogen-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 57 publications
2
71
0
2
Order By: Relevance
“…Ac-SDKP, likely by blocking inflammatory effects of Gal-3, prevents the lectin's detrimental effects on both cardiac remodeling and dysfunction. Ac-SDKP also promotes angiogenesis (16). Our laboratory previously found that Ac-SDKP stimulated endothelial cell proliferation, migration, and tube formation in vitro and increased myocardial capillary density in vivo (41).…”
Section: Discussionmentioning
confidence: 96%
“…Ac-SDKP, likely by blocking inflammatory effects of Gal-3, prevents the lectin's detrimental effects on both cardiac remodeling and dysfunction. Ac-SDKP also promotes angiogenesis (16). Our laboratory previously found that Ac-SDKP stimulated endothelial cell proliferation, migration, and tube formation in vitro and increased myocardial capillary density in vivo (41).…”
Section: Discussionmentioning
confidence: 96%
“…Ac-SDKP, the product of T␤4 hydrolysis by meprin-␣ and POP, shares very similar properties with meprin-␣. It has been reported that Ac-SDKP promotes angiogenesis in cornea (43) and abdominal wall of the rat (26). The anti-inflammatory properties of Ac-SDKP have been shown in pathologies such as renal diseases, hypertension, and cardiovascular diseases (31,45).…”
Section: Discussionmentioning
confidence: 99%
“…The antifibrotic, anti-inflammatory, and angiogenic properties of Ac-SDKP have been demonstrated in the pathology of hypertension, heart, renal, diabetes, lung, and liver and in autoimmune diseases (7,12,14,26,33,44,45). However, the mechanism of Ac-SDKP release is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular AcSDKP was measured using the AcSDKP enzyme immunoassay kit (Bertin Pharma, Montigny-le-Bretonneux, France) modified for the cells (29,39). In brief, cells were lysed with RIPA buffer containing 10 µmol/l captopril and 1 mmol/l PMSF.…”
Section: Reverse-transcription Quantitative Polymerase Chain Reactionmentioning
confidence: 99%